Penyuluhan sebagai Upaya Peningkatan Pengetahuan Hipertensi pada Lansia Di Klinik Tiara Medistra Tembung - Siregar, Julahir Hodmatua; Batubara, Saiful (INSTITUT KESEHATAN DELI HUSADA, 2023)
Hypertension is a disease that is often found in the community, especially in the elderly. This disease can cause complications so it needs to be handled properly. One way to achieve this goal is by counseling. The purpose of this community service activity is so that the community, especially the elderly, has, understands and maximizes knowledge about hypertension. The method carried out is in the form of two-way counseling using exposure with power points containing hypertension material and questionnaires before and after counseling. The target of this activity is the community/elderly patients at Tiara Medistra Clinic totaling 25 people. The implementation will be carried out on Sunday, June 22, 2023, in the clinic waiting room. After the counseling activity, a questionnaire was carried out which showed an increase in public knowledge about hypertension. The increase in knowledge is expected to make the community, especially the elderly, better able to apply this knowledge to daily life.